2015
DOI: 10.1002/etc.3176
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of fish bile extracts for monitoring endocrine disrupting chemical exposure in water: Bisphenol A, alkylphenols, and norethindrone

Abstract: The present study determined concentrations of estrogenic bisphenol A (BPA), nonylphenol, octylphenol (4-tert-octylphenol), butylphenol (4-tert-butylphenol), and progestogenic norethindrone by liquid chromatography-tandem mass spectrometry in bile extracts from field fish from the Xin'an River and market fish in Shanghai, China. Compared with the field fish, endocrine disrupting chemical (EDC) concentrations in market fish bile were at relatively high levels with high detectable rates. The average concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 41 publications
(78 reference statements)
0
15
0
4
Order By: Relevance
“… Investigating other significant persistent organic pollutants (POPs) such as Polybrominated diphenyl ethers (PBDEs) [108,109], Hexabromocyclododecane (HBCDs) [110], Endocrine disrupting chemicals (EDCs) [111], pharmaceuticals [112], etc. conducted by g-C3N4 composites under visible light irradiation and evaluating their photodegradation efficacy.…”
Section: Influence Of Environmental Conditionsmentioning
confidence: 99%
“… Investigating other significant persistent organic pollutants (POPs) such as Polybrominated diphenyl ethers (PBDEs) [108,109], Hexabromocyclododecane (HBCDs) [110], Endocrine disrupting chemicals (EDCs) [111], pharmaceuticals [112], etc. conducted by g-C3N4 composites under visible light irradiation and evaluating their photodegradation efficacy.…”
Section: Influence Of Environmental Conditionsmentioning
confidence: 99%
“…The concentration of phenolic EDsE in urban areas was especially high compared to suburban areas, so the authors concluded that an imminent risk of estrogenicity to aquatic organisms and even to humans already exists in urban areas of the river. Wu et al (2016) performed a study to determine the concentrations of BPA, NP, OP, BP, and ND in bile extract of fish collected from Xin'an River as well as those obtained from Shanghai market, China. The concentrations of EDsE on the commercially acquired fish were higher, with high detection rates compared to fish collected from the river.…”
Section: Aquatic Environmentmentioning
confidence: 99%
“…Although the use of BPA has strictly been limited, BPA is ubiquitously prevalent in manufacturing plastics and frequently leaches into water sources, resulting in bioconcentration in the environment [14,15,16,17,18]. Alarmingly, BPA can induce endocrine-disrupting health effects at modest concentrations of nanograms per liter [19,20,21,22]. …”
Section: Known Hpv Toxicantsmentioning
confidence: 99%